THE EFFECT OF PROFITABILITY AND LIQUIDITY ON COMPANY VALUE (Case Study of Banking Company on IDX 2014-2018) - Jamiah (stiatabalong.ac.id, 2023)
The development of the business world has grown rapidly, both large-scale companies and This research illustrates that the distribution of data that is a reference in the research is indicated not to be distributed correctly, because in the recapitulation of the annual financial report there are several companies that do not present complete financial statement items, this affects the analysis of processed data, small scale, one of which is to list the company on the Stock Exchange Indonesia, The purpose of this study is to determine the Effect of Profitability and Liquidity on Company Value (Case Study of Banking Companies on the Indonesia Stock Exchange 2014-2018). This study used a descriptive quantitative approach. The research sample used was 19 companies that had met the criteria that had been set with the Nonprobability sampling method with purposive sampling techniques. The results showed that the profitability variable had no effect on the Company Value It can be seen from the value of the coefficient of 0.233 and t count of 1.202 with a significance of 0.233 > 0.05 (greater than 0.05) while liquidity has no effect on the value of the company, seen from the efficiency value of -0.131 and t count of -1.152 with a significance of 0.253 > 0.05 (greater than 0.05) Keywords: Profitability; Liquidity; Company Value ; Banking; IDX